Non-contact monitoring of grouper fry weaning in recirculating aquaculture systems: Efficacy of an automated stereo vision system - Cheng-Yuan Kuo; Rung-Chi Lin; Tzong-Yueh Chen; Pei-Ju Chiang (Aquacultural Engineering, 2027)

Inhibitory effects of fruit powders on heterocyclic amine formation in charcoal-grilled pork: A comparative study of application methods and development of a functional barbecue sauce spray - Mei-Ling Li; Yu-Shun Lin; Pei-Yu Wu; Ling-Hsuan Chang; Shang-Ming Huang; Kuo-Chiang Hsu (Food Research International, 2026)

Insular divergence and host-associated diversification in ovoid-gall Daphnephila (Diptera: Cecidomyiidae) from Taiwan, with description of a new species - Sheng-Feng Lin; Tung-Chuan Chiang; Hsuan Chang; Yu-Chu Weng; Man-Miao Yang (Applied Entomology and Zoology, 2026)
The Old World cecidomyiid genus Daphnephila is primarily associated with Machilus (Lauraceae) plants and exhibits exceptionally high gall diversity in Taiwan. At present, six described species correspond to only seven of 40 known Daphnephila gall morphospecies on the island. In this study, we clarified the species identities of Taiwanese Daphnephila inducing long ovoid-galls and ovoid-galls on the leaves of five Machilus plants, and explored their diversification using molecular evidence. Accordingly, two species, D. yukawai sp. n. and D. taiwanensis , were recognized based on morphological characteristics and species delimitation method (Assemble Species by Automatic Partitioning). The former species utilizes only the endemic M . mushaensis , primarily inducing ovoid-galls along the major leaf vein, whereas the latter species associates with five Machilus species and induces two gall types on various leaf parts. Notably, when sympatric with D. yukawai sp. n., D. taiwanensis exhibits character displacement of galling habit, forming long ovoid-galls along the minor leaf veins. Furthermore, the COI-based IQ tree supported: (1) a single origin of East Asian ovoid-gall Daphnephila species, (2) the sister-group relationship between the Taiwanese lineage and a Chinese species, and (3) the role of M. mushaensis as the probable ancestral host of the Taiwanese lineage, including D. taiwanensis. These results suggest that D. taiwanensis colonized additional Machilus hosts after diverging from D. yukawai sp. n. Taken together, our findings indicate that novel plant associations and shifts in galling sites may have facilitated diversification in Daphnephila cecidomyiids, contributing to the remarkable richness of Daphnephila galls in Taiwan.

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Gut microbiota profiles across intrinsic capacity strata in community-dwelling older adults using full-length 16S rRNA sequencing - Chi-Hsien Huang; I-Cheng Lu; Chi-Wei Lin; Ming-Ta Hsieh; I-Hui Chiang; Po-Hsuan Lai; I-Ting Liu; Jung-Sheng Chen (GeroScience, 2026)

High-resolution temporal biogeochemical variations in a seagrass-coral cohabitate ecosystem: day-night, rain, and coral spawning - Huei-Ting Lin; Yu-Chen Yen; Chih-Chiang Hsieh; Hirofumi Watanabe; Yiing-Jang Yang; Hui-Yu Wang; Han Song Ong; Shi-Ming Chen; Pei-Ling Wang (Science of The Total Environment, 2026)

Sex differences in resting-state hypothalamic connectivity and its relationship with negative emotion and behavior measures in young adults - Guangfei Li; Yiran Shao; Lin Yang; Yanan Su; Mengmeng Wang; Zhao Zhang; Xiaoyi Sun; Bao Li; Xiaolin Wang; Yu Chen; Guangyu Bin; Chiang-Shan R. Li (Brain Structure and Function, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Ensemble learning: a study on the border inspection prediction model for high-risk products adulterated with Sudan Red in Taiwan - Li-Ya Wu; Wei-Chih Cheng; King-Fu Lin; Jia-Jhen Lee; Wen-Chou Lin; Hsu-Yang Lin; Chia-Yen Lu; Chih-Kang Chiang (Food Control, 2026)

Microbial-assisted copper migration stabilizes Fe/Cu cathodes for long-term bioelectro-Fenton degradation of bisphenol A - Chi-Wen Lin; Yu-Cheng Chiang; Hui Suan Ng; Shu-Hui Liu; Yi-Kai Yang (Journal of Environmental Chemical Engineering, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Intelligent circuit exercise training improves platelet mitochondrial bioenergetic efficiency in sedentary men - Ai Yin Lim; Chi-Yao Chiang; Yu-Ting Lin; Chih-Chin Hsu; Jong-Shyan Wang (European Journal of Applied Physiology, 2026)

Integrating satellite tagging and remote sensing data to model the habitat selection behaviour of dolphinfish ( Coryphaena hippurus ) in the northwestern Pacific - Kuo-Wei Yen; Shian-Jhong Lin; Sheng-Ping Wang; Ryo Kawabe; Wei-Chuan Chiang (International Journal of Remote Sensing, 2026)

Rapid Onset and Short Duration of TrenibotulinumtoxinE for Treatment of Moderate to Severe Glabellar Lines: Efficacy and Safety Results from a Phase 3 Study - Marion Moers-Carpi; Cheryl Burgess; Brian Biesman; Deirdre Hooper; Alexander Rivkin; Chung-Yi Chiang; Grace S. Park; Amy Weitzenfeld; Joan-En Chang-Lin (Toxicon, 2026)

Spatio-temporal dynamics for dolphinfish (Coryphaena hippurus) in the waters around Taiwan: Implications for stock assessment and fisheries management - Wen-Qi Xu; Sheng-Ping Wang; Chih-Yu Lin; Wei-Chuan Chiang; Toshihide Kitakado (Regional Studies in Marine Science, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Toward sustainable use of dolphinfish (Coryphaena hippurus) in the Northwest Pacific: A framework for stock assessment and management strategy evaluation - Sheng-Ping Wang; Wen-Qi Xu; Chih-Yu Lin; Toshihide Kitakado; Wei-Chuan Chiang (Regional Studies in Marine Science, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Freshwater clam aquaculture could turn inland ponds from carbon sinks into carbon sources - Wei-Jen Lin; Chien-Hsing Chiang; Chih-Chiang Tsai; Takeshi Chijimatsu; Hsing-Juh Lin (Hydrobiologia, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Functional spermidine-derivative carbon quantum dots (SPD-CQD) for disease control in shrimp - Han-You Lin; Yun-Ru Chiang (Fish & Shellfish Immunology, 2025)

Transcriptomic insights into neuroendocrine dysregulation in Macrobrachium rosenbergii infected by infectious precocity virus - Yun-Ru Chiang; Han-You Lin (Fish & Shellfish Immunology, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Streptococcal pyrogenic exotoxin a induces regulatory T cells via TNF-α-TNFR2 signaling - Chun-Hao Lu; Jason Ma; Ming-Chieh Lin; Cheng-Jang Wu; Chieh-Ying Kuo; Chuan Chiang-Ni; Ming-Ling Kuo (Medical Microbiology and Immunology, 2025)

Using an acidic vesicle tracer to identify potential bacterivores in coastal waters of the subtropical Western Pacific Ocean - Yun-Chi Lin; Yu-Chen Lin; Kuo-Ping Chiang; Chien-Pang Chin; Wen-Chen Chou (Frontiers in Marine Science, 2025)
Bacterivores play a key role in transferring energy through microbial food webs and are broadly classified as heterotrophic or mixotrophic based on the presence of inherent chloroplasts. Mixotrophs, especially in low-latitude regions, have recently gained attention due to their dual roles as primary producers and bacterial grazers, which enable them to thrive in nutrient-poor, stratified waters where traditional autotrophs or heterotrophs may be less competitive. This study investigated the composition of bacterivores in the coastal waters of northeastern Taiwan during the warm season (July and August 2022). A combination of LysoTracker staining, flow cytometry sorting, and 18S rRNA gene amplicon sequencing was used to rapidly identify heterotrophic and mixotrophic nanoflagellates (HNFs and MNFs, respectively) based on chloroplast autofluorescence. The dominant eukaryotic lineages included Alveolata, Stramenopiles, Opisthokonta, Chlorophyta, and Rhizaria. HNFs were primarily composed of MAST clades, choanoflagellates (Opisthokonta), Telonemia, and Radiolaria, while MNFs included cryptophytes, haptophytes, and chlorophytes such as Mamiella , Mantoniella and Tetraselmis , as well as stramenopiles like Dictyochophyceae and Chrysophyceae. Notably, several non-motile chlorophytes, including Chloropicon and members of Pycnococcaceae, were identified as potential bacterivores based on Lysotracker signals; however, their phagotrophic capability requires further confirmation in future studies. Despite the limitations of LysoTracker-based methods, this study reveals previously overlooked mixotrophic diversity and highlights the need for further validation. These findings advance our understanding of carbon flow and microbial dynamics in subtropical marine ecosystems under changing environmental conditions.

Effective peroxymonosulfate activation over cobalt oxide (CoO)/nitrogen-doped graphene aerogel for rhodamine b degradation - Xian-Lun Liao; Dhayanantha Prabu Jaihindh; Tzu-Ting Chang; Yi-Feng Lin; Wei-Hung Chiang; Yu-Chun Wang (Journal of Water Process Engineering, 2025)

An in vivo NanoBiT-based pseudoviral biosensor for real-time monitoring of SARS-CoV-2 spike/hACE2 interactions and therapeutic screening - Cheng-Han Lin; Meng-Wei Lin; Xin-Rui Yang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chin-Hung Tsai; Chih-Sheng Lin (Analytica Chimica Acta, 2025)

Changes in Prooxidant and Antioxidant-Related Trace Element Levels During Helicobacter pylori Eradication Therapy - Ching-Chiang Lin; Ming-Kun Ku; Hsueh-Chiao Liu; Hui-Wen Chou; Po-Chih Chen; Deng-Chyang Wu; Yeou-Lih Huang (Biological Trace Element Research, 2025)

Application of weight prediction for Holstein dairy cows in non-pregnant and postpartum stages - Hsin-I Chiang; Jia-Ming Zhou; Wen-Lin Chu (Biosystems Engineering, 2025)

Crop conversion as a strategy for enhancing water efficiency and nutrient management under climate change - Guan-Zhou Lin; Li-Chi Chiang (Journal of Hydrology, 2025)

A generalized chemical kinetics explains heterocyclic amine formation in high-temperature processed meats - Kuen-Yuh Wu; Yu-Hsuan Kuo; Pei-Chen Chao; Yu-Syuan Luo; Wan-Yu Lin; Su-Yin Chiang (Food Chemistry, 2025)

Humidity-dependent ammonium formation and enhanced light scattering in agricultural aerosols - Chien-Hao Lin; Ling-Ya Chen; Ting-Yu Chiang; Sally C. W. Tai; Shih-Yu Chang (Environmental Geochemistry and Health, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

Sustainable high-flux ceramic membrane operations for seawater pretreatment under diverse algal bloom intensities - Boyan Xu; Meiyue Ding; Kar Ming Tan; Brenda Rui Lin Tan; Tze Chiang Albert Ng; Lai Yoke Lee; Noguchi Hiroshi; Niwa Terutake; Sungwoo Bae; How Yong Ng (Water Research, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Develop intelligent waste bin prototype based on fusion feature recognition of sounds and RGB images - Wei-Chun Chen; Chieh-Feng Chiang; Yu-Hao Lin; Hao-Jun Hsieh (Waste Management, 2025)

Isolation of a new natural bromopyrrole alkaloid agenakasine, a biosynthetically related metabolite laughine, and norzooanemonin from a marine sponge Agelas nakamurai - Chung-Wei Fu; Atallah F. Ahmed; Lin Chiang; Shu-Fen Chiou; Hui-Chun Wang; Jyh-Horng Sheu (Phytochemistry Letters, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Mercury flows in a cement plant adopting circular economy policies - Liang Yu Chen; Chia Chi Hsu; Chin Lung Lin; Ming Lun Lu; Hung Lin Chiang; Moo Been Chang (Waste Management, 2025)

Mitigating non-point source pollution in tea plantations: SWAT modeling and field validation of slow-release fertilizers - Chia-Chun Ho; Pin-Chih Shih; Li-Chi Chiang; Yi-Xuan Lin; Hsiu-Feng Liu; Wen-Guei Chang; Guan-Zhou Lin (Environmental Monitoring and Assessment, 2025)

From soft to hard adventure: Examining experienced mountaineers’ mountaineering intentions through the lens of the theory of planned behavior - Shih-Shuo Yeh; Tai-Ying Chiang; Kuan-Ying Chen; Chen-Lin Lee; Tzung-Cheng Huan (Journal of Outdoor Recreation and Tourism, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

Exogenous mitochondria added on benefits for cellular prion protein overexpression in adipose-derived mesenchymal stem cells treatment on intracranial hemorrhage rat - Kun-Chen Lin; Jui-Ning Yeh; Pei‐Hsun Sung; Tsung-Cheng Yin; John Y. Chiang; Chi-Ruei Huang; Yi-Ling Chen; Yi-Ting Wang; Kuan-Hung Chen; Hon‐Kan Yip (Journal of Molecular Histology, 2025)

The influence of PM2.5 exposure on SARS-CoV-2 infection via modulating the expression of angiotensin converting enzyme II - Meng-Wei Lin; Cheng-Han Lin; Jia-Rong Chang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chih-Sheng Lin (Journal of Hazardous Materials, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Possible role of autophagy in microbial volatile pollutant-induced starch degradation and expression of hypoxia responsive genes - Chung-Chih Huang; Ching-Han Chang; Tu-Trinh Thi Truong; Wu-Guei Wang; Che-Hui Lin; Chih-Yun Chiang; Iwai Obayashi; Hao-Jen Huang (Environmental Pollution, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Additional benefits of combined ceftriaxone and adipose-derived mesenchymal stem cells on revamping the outcomes in rodent after acute spinal infection - Tsung-Cheng Yin; Hung-Sheng Lin; Pei-Hsun Sung; John Y. Chiang; Chien-Hui Yang; Hon-Kan Yip; Kuan-Hung Chen (Journal of Molecular Histology, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Response to “Letter to the Editors” regarding “A nationwide case-referent study on elevated risks of adenocarcinoma lung cancer by long-term PM2.5 exposure in Taiwan since 1997” - Wei-Chi Lin; Ruei-Hao Shie; Tzu-Hsuen Yuan; Chien-Hua Tseng; Chun-Ju Chiang; Wen-Chung Lee; Chang-Chuan Chan (Environmental Research, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Bioactive phytochemicals from the tubers of Bletilla striata Rchb.f - Chia-Lin Lee; Yun-Lian Jhan; Hsiu-Mei Chiang; Chao-Jung Chen (Natural Product Research, 2024)

Role of HIF-1α-Activated IL-22/IL-22R1/Bmi1 Signaling Modulates the Self-Renewal of Cardiac Stem Cells in Acute Myocardial Ischemia - Wei Lee; Syuan-Ling Lin; Chih-Sheng Chiang; Jui-Yu Chen; Wee-Wei Chieng; Shu-Rou Huang; Ting-Yu Chang; B. Linju Yen; Mien-Chie Hung; Kuan-Cheng Chang; Hsu-Tung Lee; Long-Bin Jeng; et al. (Stem Cell Reviews and Reports, 2024)

First telemetry insights into the movements and vertical habitat use of megamouth shark (Megachasma pelagios) in the northwest Pacific - P.J. Clerkin; M.C. Arostegui; W.C. Chiang; S.J. Lin; C.D. Miller; C.D. Braun (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Is an invasive species a notorious invader or carbon sequencer? - Karlia Meitha; Po-Yi Chen; Chieh Chang; Zi-Ci Lin; Tsai-Wen Hsu; Takashi Gojobori; Tzen-Yuh Chiang (Ecological Genetics and Genomics, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Novel compounds of Djulis ( Chenopodium formosanum Koidz ) increases collagen, antioxidants, inhibits adipogenesis - Yuan-You Lin; Yung-Kai Lin; Yung-Hsiang Lin; Chi-Fu Chiang (Natural Product Research, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Exendin-4, a glucagon-like peptide-1 receptor agonist, alleviates muscular dysfunction and wasting in a streptozotocin-induced diabetic mouse model compared to metformin - Ding-Cheng Chan; Yuan-Cheng Lin; Huei-Ping Tzeng; Rong-Sen Yang; Meng-Tsan Chiang; Shing-Hwa Liu (Tissue and Cell, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Inorganic and organic nutrients in tropical–subtropical Western Pacific coral reef waters - Huei-Ting Lin; Vianney Denis; Chih-Chiang Hsieh; Chieh-Jhen Chen; Wanchien Victoria Hsiao; Pei-Ling Wang; Chih-Chieh Su; Yan-Ning Kuo (Coral Reefs, 2024)

A nationwide case-referent study on elevated risks of adenocarcinoma lung cancer by long-term PM2.5 exposure in Taiwan since 1997 - Wei-Chi Lin; Ruei-Hao Shie; Tzu-Hsuen Yuan; Chien-Hua Tseng; Chun-Ju Chiang; Wen-Chung Lee; Chang-Chuan Chan (Environmental Research, 2024)

Small iridium clusters supported on TiO2 as catalysts for intensifying low-temperature methane activation and reforming - Hou-Jen Lai; Yu-Cheng Liu; Santhanamoorthi Nachimuthu; Shawn D. Lin; Jyh-Chiang Jiang (Chemical Engineering Journal, 2024)

Species selection as a key factor in the afforestation of coastal salt-affected lands: Insights from pot and field experiments - Tzu-Hao Su; Yang Shen; Yao-Yu Chiang; Yu-Ting Liu; Han-Ming You; Hung-Chih Lin; Kuan-Ning Kung; Yao-Moan Huang; Chih-Ming Lai (Journal of Environmental Management, 2024)

Stabilizing high-Ni cathodes with gradient surface Ti-enrichment - Wenchang Zhu; Xiaotian Zhu; Jizhen Qi; Junyi Yao; Yanbin Shen; Guanjian Cheng; Xue Huang; Shiqi Yang; Hao Zhang; Chao-Lung Chiang; Yan-Gu Lin; Jianming Bai; et al. (Chemical Engineering Journal, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Metabolomic profiling of maternal plasma identifies inverse associations of acetate and urea with anti-SARS-CoV-2 antibody titers following COVID-19 vaccination during pregnancy - An-Shine Chao; Chiao-Yun Lin; Meng-Han Chiang; Kuan-Ying Lu; Cheng-Kun Tsai; Kuan-Ju Chen; Chih-Wei Chien; Ting-Shu Wu; Yao-Lung Chang; Angel Chao; Gigin Lin; Chih-Yung Chiu (Journal of Molecular Medicine, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Diversity and distribution of small-sized planktonic ciliate communities in the East China Sea - Wei-Ting Chen; Yun-Chi Lin; Sheng-Fang Tsai; Kuo-Ping Chiang (Frontiers in Marine Science, 2024)
Ciliates are an important ecological component in the microbial food web, but few studies have been conducted on the spatial distribution of small-sized planktonic ciliate communities in the East China Sea (ECS). Investigating ciliate communities using conventional morphological approaches is particularly difficult for the small, fragile, and naked species. Therefore, we applied DNA metabarcoding analysis to explore the spatial pattern of small-sized planktonic ciliate community structure within the surface, deep chlorophyll maximum (DCM), and bottom layers. Results showed the cosmopolitan species, Leegaardiella sp., was dominant and widespread in the ECS. The relative abundance of the mixotrophic family Tontonnidae decreased in the deeper layer. We characterized water masses of the ECS using environmental variables. In nano-sized ciliate communities, non-metric multidimensional scaling (NMDS) plots revealed a correlation with temperature, salinity, density, and depth. The circulation patterns were similar to cluster analysis results, suggesting that hydrographic conditions shaped small-sized ciliate community composition.

Extinction coefficient of dry and deliquescent chemical components of PM_(2.) 5 in urban areas and their impacts on visibility deterioration - Chien-Hao Lin; Shao-En Sun; Chung-Te Lee; Ting-Yu Chiang; Shih-Yu Chang; Tzu-Shuan Wu; Hsin-Yu Wei; Ling-Ya Chen; Hao-Wei Liu; Sally C.W. Tai (Atmospheric Pollution Research, 2024)

Comparative analysis of Deinagkistrodon acutus venom from Taiwan and China utilizing chromatographic, electrophoretic, and bioinformatic approaches, along with ELISA employing a monospecific antivenom - Tein-Shun Tsai; Inn-Ho Tsai; Jing-Lin Qiu; Yuen-Ying Chan; Yu-Wei Chiang (Toxicon, 2024)

Quantitative analysis of infectious precocity virus load and stunted growth syndrome via an immunohistochemical assay and reverse transcriptase quantitative real-time PCR in Macrobrachium rosenbergii - Yun-Ru Chiang; Ya-Yun Lu; Han-You Lin (Aquaculture, 2024)

A memory-rich conjugated microporous polymer-based electrochromic framework through two-in-one metal catalyst free route - Gaurav Kumar Silori; Szu-Chia Chien; Li-Chiang Lin; Kuo-Chuan Ho (Chemical Engineering Journal, 2024)

Tri-objective Stochastic Model to Optimize Location and Sizing of Scooter Battery Swapping Station - Yu-Hao Lin; Ping-Yu Liu; Chieh-Feng Chiang (Sustainable Cities and Society, 2024)

Towards a use of waste polyethylene in asphalt mixture as a compaction aid - Chi-Lin Chiang; Maziar Mivehchi; Haifang Wen (Journal of Cleaner Production, 2024)

Two-stage conversion of CO2 to methanol and dimethyl ether using CuO–ZnO–Al2O3/protonated Y-type zeolite catalysts - Kuen-Song Lin; Abrar Hussain; Nguyen Tien Thao; Jamshid Hussain; Chao-Lung Chiang (Journal of Environmental Chemical Engineering, 2024)

Treatment of Moderate-to-Severe Glabellar Lines With RelabotulinumtoxinA, an Investigational Liquid Botulinum Toxin: Clinical Efficacy and Safety Results From the READY-1 Phase 3 Trial - Nowell Solish; Amir Moradi; Sachin Shridharani; Lisa Donofrio; Michael H Gold; Brian Biesman; Melissa Chiang; Rosalyn George; Kristel Polder; Rob Schwarcz; Xiaoming Lin; Sarah Coquis-Knezek (Toxicon, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Highly effective degradation of ibuprofen by alkaline metal-doped copper oxides via peroxymonosulfate activation: Mechanisms, degradation pathway and toxicity assessments - Meng-Wei Zheng; Cheng-Wei Lin; Pei-Hsin Chou; Chao-Lung Chiang; Yan-Gu Lin; Shou-Heng Liu (Journal of Hazardous Materials, 2024)

Plasma-engineered graphene quantum dot-based nanocomposites as smart CO2-philic membranes with extremely high separation performance - Yi-Jui Yeh; Wei Lin; Wei-Hung Chiang; Kuo-Lun Tung (Chemical Engineering Journal, 2023)

Interplay Between Inflammatory-immune and Interleukin-17 Signalings Plays a Cardinal Role on Liver Ischemia-reperfusion Injury—Synergic Effect of IL-17Ab, Tacrolimus and ADMSCs on Rescuing the Liver Damage - Sheung-Fat Ko; Yi-Chen Li; Pei-Lin Shao; John Y. Chiang; Pei-Hsun Sung; Yi-Ling Chen; Hon-Kan Yip (Stem Cell Reviews and Reports, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Neuroprotective Effects of Probiotic Lactobacillus reuteri GMNL-263 in the Hippocampus of Streptozotocin-Induced Diabetic Rats - Jing-Ying Lin; Bruce Chi-Kang Tsai; Hui-Chuan Kao; Chien-Yi Chiang; Yun-An Chen; William Shao-Tsu Chen; Tsung-Jung Ho; Chun-Hsu Yao; Wei-Wen Kuo; Chih-Yang Huang (Probiotics and Antimicrobial Proteins, 2023)

Carbon footprint of offshore platform in Indonesia using life cycle approach - Aditya Prana Iswara; Aulia Ulfah Farahdiba; Rachmat Boedisantoso; Anwar Rosyid; Sunu Priambodo; Lin-Han Chiang Hsieh (Environment, Development and Sustainability, 2023)

A concise chemoenzymatic total synthesis of neutral Globo-series glycosphingolipids Globo A and Globo B, and Forssman and para-Forssman antigens - Yu-Ching Chiang; Chun-Yen Wu; Pei-Yun Chiang; Avijit K. Adak; Chun-Cheng Lin (Glycoconjugate Journal, 2023)

Exposure to incense burning, biomarkers, and the physical health of temple workers in Taiwan - Su-Er Guo; Pamela A. Ratner; Sung-Chih Tseng; Chieh-Mo Lin; Miao-Ching Chi; Chiang-Wen Lee; Ying-Chun Yu (Environmental Science and Pollution Research, 2023)
Incense burning releases heavy particulate matter (PM) and nitrogen dioxide (NO 2 ), known to have adverse effects on human health. Long-term exposure to PM and NO 2 increases inflammatory cytokine levels and can induce respiratory diseases. This study examined the association between incense burning exposure and the health status, especially inflammatory biomarkers, of temple workers and volunteers in Taiwan. The longitudinal observational study compared adult temple workers and volunteers, with long-term incense burning exposure, to residents from outpatient clinics in the Chiayi area. Forced expiratory volume in 1 s (FEV1) and serum and exhaled breath condensate (EBC) cytokines were assessed. Nonparametric Mann-Whitney U tests were used to compare cytokine levels of the exposure and control groups during the cold and hot weather seasons. FEV1 was significantly more diminished in the exposed group than in the control group during the cold season. Exposure status was associated with greater hot-cold seasonal differences in serum interleukins (IL)-1β (regression coefficient ( B ) = 6.6, 95% confidence interval (CI) = 5.0 to 8.3, p < .001), IL17-A ( B = 2.4, 95% CI = 0.3 to 4.5, p = .03), and plasminogen activator inhibitor [PAI]-1 ( B = 5.4, 95% CI = 1.5 to 9.3, p = .009). After adjusting for confounders, the groups’ serum levels of IL-1β, IL-17A, and PAI-1 significantly differed. EBC cytokines did not show significant differences. Elevated levels of IL-1β, IL17-A, and PAI-1 have been associated with various autoinflammatory syndromes and diseases. Given the cultural significance of incense burning, culturally sensitive interventions, including education, policy development, and program implementation, are crucial to protect individuals’ health, especially temple workers, from the adverse effects of exposure, addressing the manufacture, importation, and sale of incense.

Direct synthesis of CH3OH from CO2 hydrogenation over Ni5Ga3/SiO2 catalysts - Kuen-Song Lin; Abrar Hussain; You-Sheng Lin; Yung-Chen Hsieh; Chao-Lung Chiang (Fuel, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Air quality health index (AQHI) based on multiple air pollutants and mortality risks in Taiwan: Construction and validation - Mu-Jean Chen; Yue Leon Guo; Pinpin Lin; Hung-Che Chiang; Pau-Chung Chen; Yu-Cheng Chen (Environmental Research, 2023)

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Phyllanthus emblica L. extract alleviates leptin resistance and lipid accumulation by inhibiting methylglyoxal production - Yue-Ning Huang; Sheng-Yi Chen; Jer-An Lin; I-Chen Chiang; Gow-Chin Yen (Food Bioscience, 2023)

Sulfur-induced electronic optimization of Mo5N6 for hydrogen evolution through topochemical substitution - Jianmei Chen; Xiaochun Liu; Hao Wang; Chao-Lung Chiang; Pengfei Hou; Jianmin Li; Huanyu Jin; Shujuan Liu; Xing Meng; Yan-Gu Lin; Jong-Min Lee; Qiang Zhao (Chemical Engineering Journal, 2023)

Movement patterns and habitat use of adult giant trevally (Caranx ignobilis) in the South China Sea - Wei-Chuan Chiang; Shian-Jhong Lin; Ker-Yea Soong; Te-Yu Liao; Yu-Yun Chen; Yuan-Shing Ho; Chen-Te Tseng; Michael K. Musyl (Marine Biology, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Evaluating the waste and CO2 reduction potential of packaging by reuse model in supermarkets in Taiwan - Hsin-Tien Lin; Cian-Wei Chiang; Jhao-Ning Cai; Hsin-Yu Chang; Yu-Nien Ku; Falk Schneider (Waste Management, 2023)

Hyperbaric Oxygen Therapy Attenuated the Motor Coordination and Cognitive Impairment of Polyglutamine Spinocerebellar Ataxia SCA17 Mice - Meng-Ke Chiang; Ta-Chun Lin; Keng-Hsuan Lin; Ya-Chin Chang; Hsiu Mei Hsieh-Li; Dar-Ming Lai (The Cerebellum, 2023)

Clay nanosheets simultaneously intercalated and stabilized by PEGylated chitosan as drug delivery vehicles for cancer chemotherapy - Hsuan-Jung Huang; Shih-Yu Huang; Tzu-Hao Wang; Tzu-Yun Lin; Nan-Ching Huang; Orion Shih; U-Ser Jeng; Che-Yi Chu; Wen-Hsuan Chiang (Carbohydrate Polymers, 2023)

Editorial: Oceanographic processes linking nearshore, continental shelf, and shelf break - Feng-Hsun Chang; Yun-Chi Lin; Kuo-Ping Chiang; Ya-Han Nien; Chih-hao Hsieh; Wei-Jen Chen; Chin-Chang Hung; Toru Kobari; Hiroaki Saito; William Savidge (Frontiers in Marine Science, 2023)

Dynamic Co-Simulation Analysis and Control of an IEA 15 MW Offshore Floating Semi-Submersible Wind Turbine under Taiwan Offshore-Wind-Farm Conditions of Wind and Wave - Cherng-Jer Chueh; Chun-Hung Chien; Ching Lin; Ting-Yan Lin; Mao-Hsiung Chiang (Journal of Marine Science and Engineering, 2023)
This study aims to develop dynamic co-simulation and control for analyzing the IEA 15 MW semi-submersible floating wind turbine under Taiwan offshore-wind-farm conditions of wind and wave. The IEA 15 MW wind turbine is mounted on a UMaine VolturnUS-S reference platform with a mooring system designed for a water depth of 70 m, in this study. The dynamic co-simulation combines software of SIMPACK, MATLAB/SIMULINK, AeroDyn, HydroDyn, WAMIT, and MAP++ to achieve the complex dynamic simulation of aerodynamics, hydrodynamics, mechanism dynamics and control system dynamics. In addition, this study proposes a novel power-control strategy combining fuzzy sliding-mode control with additional pitching-rate feedback. Since the motion of the floating platform, especially the pitching motion, contributes to power oscillation, the proposed novel power-control strategy with additional pitching-rate feedback can reduce the influence of the floating-platform oscillation motion, and is verified under different conditions.

Evaluating the release and metabolism of ricinine from castor cake fertilizer in soils using a LC-QTOF/MS coupled with SIRIUS workflow - Kai-Xuan Zheng; Cheng-Hua Liu; Sichao Wang; Yu-Min Tzou; Chih-Min Chiang; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Ya-Hui Chuang (Chemosphere, 2023)

Realizing the bifunctional electrocatalysis via local charge rearrangement of α-CrOOH-modulated Co@CoMoOx for overall water splitting - Suh-Ciuan Lim; Chao-Lung Chiang; Chun-Kuo Peng; Wen-Bin Wu; Yu-Chang Lin; Yu-Ru Lin; Chi-Liang Chen; Yan-Gu Lin (Chemical Engineering Journal, 2023)

Lytic Bacteriophage as a Biomaterial to Prevent Biofilm Formation and Promote Neural Growth - Zi-Hao Liu; Ming-Tse Chiang; Hsin-Yi Lin (Tissue Engineering and Regenerative Medicine, 2022)

Theranostic Radiolabeled Nanomaterials for Molecular Imaging and potential Immunomodulation Effects - Chao-Cheng Chen; Yang-Hsiang Chan; Syue-Liang Lin; Huihua Kenny Chiang; Yi-Jang Lee; Hui-Yen Chuang (Journal of Medical and Biological Engineering, 2022)

How can sports entrepreneurs achieve their corporate sustainable development goals under the COVID-19 epidemic? - Kuo Chiang Ting; Hsiao-Hsien Lin; Jung-Hul Chien; Kuan-Chieh Tseng; Chin-Hsien Hsu (Environmental Science and Pollution Research, 2022)

Vibrio salinus sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll in the western Pacific Ocean - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2022)

A multi-step nitrifying microbial enrichment to remove ammonia and nitrite in brackish aquaculture systems - Dao Thi Anh Tuyet; Le Minh Hiep; Ha Thi Binh; Le Thanh Huyen; Sen-Lin Tang; Pei-Wen Chiang; Do Manh Hao (Biodegradation, 2022)

The Spatial Variation in Chlorophyte Community Composition From Coastal to Offshore Waters in a Subtropical Continental Shelf System - Yun-Chi Lin; Chien-Pang Chin; Wei-Ting Chen; Ching-Ting Huang; Gwo-Ching Gong; Kuo-Ping Chiang; Xin-Bei Chen (Frontiers in Marine Science, 2022)
Globally, the continental shelf occupies less than 10% of the total sea surface, but supports substantial primary production and fisheries. Photosynthetic picoeukaryotes (PPE) are important primary producers in marine ecosystems, and chlorophytes make a significant contribution to PPE abundance. Although the distribution of chlorophytes has been widely studied, little is known about how their community composition varies along the coastal-offshore gradient in subtropical continental shelf waters. To better understand their spatial variations, we employed metabarcoding data of 18S rRNA V4 gene to examine chlorophyte composition within the surface and deep chlorophyll maximum (DCM) layers over the continental shelf in the East China Sea (ECS) with high-resolution sampling. Our results indicate a higher chlorophyte diversity in the surface layer than in the DCM. In addition, we found that chlorophytes in oligotrophic Kuroshio surface water were the most diverse, with a higher percentage of Chloropicophyceae, prasinophyte clade V, prasinophyte clade IX, Palmophyllophyceae and Chlorodendrophyceae. In more eutrophic waters along the coast and within the DCM layer, chlorophytes were dominated by Mamiellophyceae. A significant spatial variation in community composition occurred along the nutrient gradient in the subtropical continental shelf ecosystem, varying from Mamiellophyceae-dominant in coastal water to Chloropicophyceae-dominant in offshore water. Furthermore, at a low saline coastal station, which had the lowest chlorophyte diversity, Picochlorum (Trebouxiophyceae) was dominant. Overall, chlorophyte diversity was positively correlated with temperature, and negatively correlated with silicate concentration. This study revealed that terrestrial input into continental systems influences chlorophyte diversity in the subtropical northwestern Pacific Ocean.

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Characterization of chemical constituents with their antioxidant and anti-melanogenesis activities from the roots of Ampelopsis japonica - Chia-Lin Lee; Yun-Lian Jhan; Hsiu-Mei Chiang; Yi-Hung Chen; Chao-Jung Chen; Yuan-Shiun Chang (Natural Product Research, 2022)

Should Plate-Bone Gap be Preserved in Far-Cortical Locking Technique? A Biomechanical Study - Shun-Ping Wang; Yang-Chen Chou; Cheng-En Hsu; Chi-Wen Chou; Chao-Ping Chen; Kun-Jhih Lin; Fuu-Cheng Jiang; Wen-Chuan Chen; Chen-Chiang Lin (Journal of Medical and Biological Engineering, 2022)

Functional connections between bird eggshell stiffness and nest characteristics through risk of egg collision in nests - Chih‐Ming Hung; Shu‐Han Tsao; Pei‐Lin Chiang; Shang‐Ping Wu; Mao‐Ning Tuanmu; Jia‐Yang Juang (Ecology Letters, 2022)
Eggs and nests are two critical traits for the ecological success of birds. Their functional interactions, however, remain unclear. Here, we examined the functional connections between egg stiffness and nest attachment, site and structure for 1350 avian species. We revealed high eggshell stiffness for eggs in nests with a pensile attachment, located on non‐tree vegetation or having a domed shape, suggesting that birds produce stiffer eggs in response to higher egg‐collision risk in unstable or enclosed nests. Interdependence models suggested that the evolution of eggshell stiffness was more likely to be driven by than drive that of nest characters. Our results implied a trade‐off between investment in competing for established nesting niches and producing stiff eggs to explore novel niches with high collision risk, possibly mediated by predation or thermoregulation. This study highlights an overlooked connection between nests and eggshells that may have broadened the ecological niches of birds.

Probiotics and their Metabolites Reduce Oxidative Stress in Middle-Aged Mice - Wen-Yang Lin; Jia-Hung Lin; Yi-Wei Kuo; Pei-Fang Rose Chiang; Hsieh-Hsun Ho (Current Microbiology, 2022)
Aging is an irreversible physiological degradation of living organisms. Accumulated oxidative stress and dysbiosis accelerate aging. Probiotics such as Lactobacillus and Bifidobacterium and their fermented metabolites (postbiotics) have been discovered to exhibit antioxidative activities that regulate oxidative stress and protect cells from oxidative damage. We screened selected Lactobacillus and Bifidobacterium strains and their postbiotics for potential antioxidative activity by using DPPH (2,2-Diphenyl-1-picrylhydrazyl) assay. Strains with their metabolites were selected for mixed formula in experiments involving aging mice. The aged groups presented higher oxidative stress in the brain, liver, heart, and kidney than did young mice. However, treatment with probiotic strains and their postbiotics elevated antioxidative levels, especially in the high-dose probiotics plus postbiotics group. Next-generation sequencing data revealed positive microbiota alterations of Lactobacillus and Bifidobacterium and Akkermansia in the gut. Lactobacillus johnsonii and Akkermansia muciniphila exhibited effective enlargement of relative abundance. Besides, high-dose probiotics and high-dose probiotics plus postbiotics showed significant elevation in serum SCFAs, especially in butyrate. In conclusion, the formula containing Bifidobacterium animalis subsp. infantis BLI-02, Bifidobacterium breve Bv889, Bifidobacterium bifidum VDD088, B. animalis subsp. lactis CP-9, and Lactobacillus plantarum PL-02 and their metabolites may benefit aged people’s health.

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

Rac1 and Akt Exhibit Distinct Roles in Mediating Aβ-Induced Memory Damage and Learning Impairment - Kuan-Chung Cheng; Ying-Hao Chen; Chia-Lin Wu; Wang-Pao Lee; Chun Hei Antonio Cheung; Hsueh-Cheng Chiang (Molecular Neurobiology, 2021)

Exercise renovates H2S and Nrf2-related antioxidant pathways to suppress apoptosis in the natural ageing process of male rat cortex - Jing-Ying Lin; Tsung-Jung Ho; Bruce Chi-Kang Tsai; Chien-Yi Chiang; Hui-Chuan Kao; Wei-Wen Kuo; Ray-Jade Chen; Vijaya Padma Viswanadha; Chi-Wen Huang; Chih-Yang Huang (Biogerontology, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

The Individual and Synergistic Indexes for Assessments of Heavy Metal Contamination in Global Rivers and Risk: a Review - Hong-Giang Hoang; Chitsan Lin; Chow-Feng Chiang; Xuan-Thanh Bui; Wisanukorn Lukkhasorn; Thi-Phuong-Thuy Bui; Huu-Tuan Tran; Thi-Dieu-Hien Vo; Van-Giang Le; Long D. Nghiem (Current Pollution Reports, 2021)

Vibrio nitrifigilis sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Orographic effects on the propagation and rainfall modification associated with the 2007–08 Madden–Julian oscillation (MJO) past the New Guinea Highlands - Yuh-Lang Lin; William Agyakwah; Justin G. Riley; Huang-Hsiung Hsu; Li-Chiang Jiang (Meteorology and Atmospheric Physics, 2021)

Does technology advancement reduce aggregate carbon dioxide emissions? Evidence from 66 countries with panel threshold regression model - Ruzi Li; Lin Lin; Lei Jiang; Yaobin Liu; Chien-Chiang Lee (Environmental Science and Pollution Research, 2021)

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Improving Image Correlation and Differentiation of 3D Endoluminal Lesions in the Air Spaces Using a Novel Target Gray Level Mapping Technique: A Preliminary Study of Its Application to Computed Tomographic Colonography and Comparison with Traditional Surface Rendering Method - Lih-Shyang Chen; Ta-Wen Hsu; Shao-Jer Chen; Shu-Han Chang; Chih-Wen Lin; Yu-Ruei Chen; Chin-Chiang Hsieh; Shu-Chen Han; Ku-Yaw Chang; Chun-Ju Hou (Journal of Medical and Biological Engineering, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Neglect of Presence of Bacteria Leads to Inaccurate Growth Parameters of the Oligotrich Ciliate Strombidium sp. During Grazing Experiments on Nanoflagellates - Wan-Lin Chen; Kuo-Ping Chiang; Sheng-Fang Tsai (Frontiers in Marine Science, 2020)

(–)-β-Homoarginine anhydride, a new antioxidant and tyrosinase inhibitor, and further active components from Trichosanthes truncata - I-Ting Weng; Yen-An Lin; Guan-Yu Chen; Hsiu-Mei Chiang; Yi-Jung Liu; Chao-Jung Chen; Yu-Hsuan Lan; Chia-Lin Lee (Natural Product Research, 2020)

Ecological risk assessment of species impacted by fisheries in waters off eastern Taiwan - Chih‐Yu Lin; Sheng‐Ping Wang; Wei‐Chuan Chiang; Shane Griffiths; Hsin‐Ming Yeh (Fisheries Management and Ecology, 2020)
An ecological risk assessment was undertaken using productivity‐susceptibility analysis (PSA) to determine the relative vulnerability of 52 species caught by fisheries in the waters off eastern Taiwan. Overall, eight and 20 species were classified as having high and moderate vulnerability, respectively, and the remaining 24 species were classified as having low vulnerability. The species with the highest vulnerability scores were caught mainly by longline and gillnet fisheries, highlighting the need for improved data collection to facilitate a more detailed investigation using more quantitative methods. The data quality analysis indicated that the quality of data was classified as “moderate” for economically important species. However, many species were considered data‐limited and thus collecting high‐resolution catch and effort information and conducting biological studies, especially relating to age, growth and reproduction, are recommended to improve the reliability of outputs from data‐limited assessments such as PSA.

Technology on sleep surgery - Wei Zhao; Lianhua Zhao; Yuanqing Zhao; Zaiyu Guo; Jialiang Guo; Cunguo Lin; Rayleigh Ping-Ying Chiang (Sleep and Biological Rhythms, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Diverse Community Structures in the Neuronal-Level Connectome of the Drosophila Brain - Chi-Tin Shih; Yen-Jen Lin; Cheng-Te Wang; Ting-Yuan Wang; Chih-Chen Chen; Ta-Shun Su; Chung-Chuang Lo; Ann-Shyn Chiang (Neuroinformatics, 2020)

Depositional influence of submarine channel migration on thermal properties of the Lower Fangliao Basin, offshore southwestern Taiwan - Feisal Dirgantara; Hsieh-Tang Chiang; Andrew Tien-Shun Lin; Char-Shine Liu; Song-Chuen Chen (Marine Geophysical Research, 2020)

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

Managing water quality in a river basin with uncertainty - H.-W. Chen; W.-Y. Chen; C.-T. Wang; Y.-H. Lin; M.-J. Deng; C.-Y. Chiang (International Journal of Environmental Science and Technology, 2020)

The High-Frequency Decay Parameter (Kappa) in Taiwan - Shun-Chiang Chang; Kuo-Liang Wen; Ming-Wey Huang; Chun-Hsiang Kuo; Che-Min Lin; Chun-Te Chen; Jyun-Yan Huang (Pure and Applied Geophysics, 2019)

Movement behaviour of released wild and farm-raised dolphinfish Coryphaena hippurus tracked by pop-up satellite archival tags - Shian-Jhong Lin; Michael K. Musyl; Sheng-Ping Wang; Nan-Jay Su; Wei-Chuan Chiang; Ching-Ping Lu; Kazuki Tone; Chang-Ying Wu; Akira Sasaki; Itsumi Nakamura; Kazuyoshi Komeyama; Ryo Kawabe (Fisheries Science, 2019)

A Modular Data Glove System for Finger and Hand Motion Capture Based on Inertial Sensors - Bor-Shing Lin; I-Jung Lee; Pei-Ying Chiang; Shih-Yuan Huang; Chih-Wei Peng (Journal of Medical and Biological Engineering, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Changes in Trace Elements During Early Stages of Chronic Kidney Disease in Type 2 Diabetic Patients - Ching-Chiang Lin; Ching-Tang Shih; Chien-Hung Lee; Yeou-Lih Huang (Biological Trace Element Research, 2018)

The Divalent Elements Changes in Early Stages of Chronic Kidney Disease - Wan-Ju Kung; Ching-Tang Shih; Chien-Hung Lee; Ching-Chiang Lin (Biological Trace Element Research, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Seasonal variation and source apportionment of PM2.5-bound trace elements at a coastal area in southwestern Taiwan - Su-Lun Hwang; Miao-Ching Chi; Su-Er Guo; Yu-Ching Lin; Chiang-Ting Chou; Chieh-Mo Lin (Environmental Science and Pollution Research, 2018)

Residue characteristics of sludge from a chemical industrial plant by microwave heating pyrolysis - Kuo-Hsiung Lin; Nina Lai; Jun-Yan Zeng; Hung-Lung Chiang (Environmental Science and Pollution Research, 2018)

Molecular screening of multidrug-resistance tuberculosis by a designated public health laboratory in Taiwan - H.-C. Lin; C.-L. Perng; Y.-W. Lai; F.-G. Lin; C.-J. Chiang; H.-A. Lin; R. Jou; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Strategic Behavior in Certifying Green Buildings: An Inquiry of the Non-building Performance Value - Lin-Han Chiang Hsieh; Douglas Noonan (Environmental Management, 2017)

Tissue and cell-type co-expression networks of transcription factors and wood component genes in Populus trichocarpa - Rui Shi; Jack P. Wang; Ying-Chung Lin; Quanzi Li; Ying-Hsuan Sun; Hao Chen; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2017)

Gonorrhea infection increases the risk of prostate cancer in Asian population: a nationwide population-based cohort study - Y.-C. Wang; C.-H. Chung; J.-H. Chen; M.-H. Chiang; Ti-Yin; C.-H. Tsao; F.-H. Lin; W.-C. Chien; S.-T. Shang; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Retraction Note to: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

An integrated earthquake early warning system and its performance at schools in Taiwan - Bing-Ru Wu; Nai-Chi Hsiao; Pei-Yang Lin; Ting-Yu Hsu; Chiou-Yun Chen; Shieh-Kung Huang; Hung-Wei Chiang (Journal of Seismology, 2017)

The summer distribution of coccolithophores and its relationship to water masses in the East China Sea - Lee-Kuo Kang; Hsing-Ming Lu; Pei-Ting Sung; Ya-Fan Chan; Yun-Chi Lin; Gwo-Ching Gong; Kuo-Ping Chiang (Journal of Oceanography, 2016)

Functional composition drives ecosystem function through multiple mechanisms in a broadleaved subtropical forest - Jyh-Min Chiang; Marko J. Spasojevic; Helene C. Muller-Landau; I-Fang Sun; Yiching Lin; Sheng-Hsin Su; Zueng-Sang Chen; Chien-Teh Chen; Nathan G. Swenson; Ryan W. McEwan (Oecologia, 2016)

Exploring the Mechanism of Surface and Ground Water through Data-Driven Techniques with Sensitivity Analysis for Water Resources Management - Wen-Ping Tsai; Yen-Ming Chiang; Jun-Lin Huang; Fi-John Chang (Water Resources Management, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Maternal exposure to di-(2-ethylhexyl) phthalate exposure deregulates blood pressure, adiposity, cholesterol metabolism and social interaction in mouse offspring - Kuan-I Lee; Chin-Wei Chiang; Hui-Ching Lin; Jin-Feng Zhao; Cheng-Ta Li; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Molecular Characterization of Ethylene Response Sensor 1 (BoERS1) in Bambusa oldhamii - Yi-Lin Hsieh; Ching-Fang Lu; Bing-Yu Chiang; Shu-Chien Liao; Rita P.-Y. Chen; Choun-Sea Lin; Ai-Yu Wang; Chien-Chih Yang (Plant Molecular Biology Reporter, 2016)

Mono(2-ethylhexyl)phthalate accumulation disturbs energy metabolism of fat cells - Huai-chih Chiang; Ya-Ting Kuo; Chih-Che Shen; Yi-Hua Lin; Shu-Li Wang; Tsui-Chun Tsou (Archives of Toxicology, 2016)

Rainfall-Runoff Prediction Using Dynamic Typhoon Information and Surface Weather Characteristic Considering Monsoon Effects - Chih-Chiang Wei; Nien-Sheng Hsu; Chien-Lin Huang (Water Resources Management, 2016)

Typhoon Disturbance Mediates Elevational Patterns of Forest Structure, but not Species Diversity, in Humid Monsoon Asia - Chung-How Chi; Ryan W. McEwan; Chung-Te Chang; Chengyang Zheng; Zhijie Yang; Jyh-Min Chiang; Teng-Chiu Lin (Ecosystems, 2015)

RETRACTED ARTICLE: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2015)

Robust Endoplasmic Reticulum-Associated Degradation of Rhodopsin Precedes Retinal Degeneration - Wei-Chieh Chiang; Heike Kroeger; Sanae Sakami; Carissa Messah; Douglas Yasumura; Michael T. Matthes; Judith A. Coppinger; Krzysztof Palczewski; Matthew M. LaVail; Jonathan H. Lin (Molecular Neurobiology, 2015)

Expression of eggplant ascorbate peroxidase increases the tolerance of transgenic rice plants to flooding stress - Chih Ming Chiang; Long Fang O. Chen; Shang Wen Shih; Kuan Hung Lin (Journal of Plant Biochemistry and Biotechnology, 2015)

Genetic relationships and ecological divergence in Salix species and populations in Taiwan - Chun-Lin Huang; Chung-Te Chang; Bing-Hong Huang; Jeng-Der Chung; Jui-Hung Chen; Yu-Chung Chiang; Shih-Ying Hwang (Tree Genetics & Genomes, 2015)

A new design method for extracorporeal high-intensity focused ultrasound annular array - Gin-Shin Chen; Yu-Cheng Lin; Chu-Chiang Chen (Medical & Biological Engineering & Computing, 2015)

Pilot study of mold in homes of asthmatic children in Taipei, Taiwan, using the Environmental Relative Moldiness Index - Chi-Hsien Chen; H. Jasmine Chao; Wei-Chiang Shen; Bing-Yu Chen; King-Teh Lin; Yue Leon Guo; Stephen Vesper (Aerobiologia, 2015)

Duodenal Neuroendocrine Carcinoma Presenting with Disseminated Liver and Bone Metastases as the Primary Manifestation: Case Report and Literature Review - Tao Guo; Ka Kei Ng; Hoi Wan Chiang; Man Fei Ma; Yi Lin; Jia Ming Qian (Cell Biochemistry and Biophysics, 2015)

Development, characterization and cross-species amplification of new microsatellite primers from an endemic species Cinnamomum kanehirae (Lauraceae) in Taiwan - Kuo-Hsiang Hung; Chia-Hung Lin; Huei-Chuan Shih; Yu-Chung Chiang; Li-Ping Ju (Conservation Genetics Resources, 2014)

Development of an empirical model for rainfall-induced hillside vulnerability assessment: a case study on Chen-Yu-Lan watershed, Nantou, Taiwan - Tsu-Chiang Lei; Yi-Min Huang; Bing-Jean Lee; Meng-Hsun Hsieh; Kuan-Ting Lin (Natural Hazards, 2014)

Galectin-1 induces vascular permeability through the neuropilin-1/vascular endothelial growth factor receptor-1 complex - Ming-Heng Wu; Nien-Wen Ying; Tse-Ming Hong; Wei-Fan Chiang; Yueh-Te Lin; Yuh-Ling Chen (Angiogenesis, 2014)

Development and characterization of nine polymorphic microsatellite markers from the sword prawn Parapenaeopsis hardwickii using PCR-based isolation of microsatellite arrays (PIMA) - Chuan-Wen Ho; Tzong-Der Tzeng; Tzen-Yuh Chiang; Chih-Yao Li; Feng-Jiau Lin (Conservation Genetics Resources, 2014)

Different Visible Colors and Green Fluorescence Were Obtained from the Mutated Purple Chromoprotein Isolated from Sea Anemone - Cheng-Yi Chiang; Yi-Lin Chen; Huai-Jen Tsai (Marine Biotechnology, 2014)

Expression of the broccoli catalase gene (BoCAT) enhances heat tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Shi-Peng Chen; Long-Fang O. Chen; Ming-Chang Chiang; Hao-Lun Chien; Kuan-Hung Lin (Journal of Plant Biochemistry and Biotechnology, 2014)

Characteristics of endogenous γ-aminobutyric acid (GABA) in human platelets: functional studies of a novel collagen glycoprotein VI inhibitor - Kuan-Hung Lin; Wan-Jung Lu; Shwu-Huey Wang; Tsorng-Harn Fong; Duen-Suey Chou; Chao-Chien Chang; Nen-Chung Chang; Yung-Chen Chiang; Shih-Yi Huang; Joen-Rong Sheu (Journal of Molecular Medicine, 2014)

Cloning and gene expression analysis of sponge gourd ascorbate peroxidase gene and winter squash superoxide dismutase gene under respective flooding and chilling stresses - Chih Ming Chiang; Wen Shuo Kuo; Kuan Hung Lin (Horticulture, Environment, and Biotechnology, 2014)

Demography of the upward-shifting temperate woody species of the Rhododendron pseudochrysanthum complex and ecologically relevant adaptive divergence in its trailing edge populations - Chia-Ying Chen; Bo-Kai Liang; Jeng-Der Chung; Chung-Te Chang; Yi-Chiang Hsieh; Teng-Chiu Lin; Shih-Ying Hwang (Tree Genetics & Genomes, 2014)

Unraveling the complex genetic model for cystic fibrosis: pleiotropic effects of modifier genes on early cystic fibrosis-related morbidities - Weili Li; David Soave; Melissa R. Miller; Katherine Keenan; Fan Lin; Jiafen Gong; Theodore Chiang; Anne L. Stephenson; Peter Durie; Johanna Rommens; Lei Sun; Lisa J. Strug (Human Genetics, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Two-Stage Pumping Control Model for Flood Mitigation in Inundated Urban Drainage Basins - Chih-Chiang Wei; Nien-Sheng Hsu; Chien-Lin Huang (Water Resources Management, 2014)

Altered molecular repertoire of immune system by renal dysfunction in the elderly: is prediction and targeted prevention in the horizon? - Cheng-Lin Lang; Min-Hui Wang; Kuan-Yu Hung; Chih-Kang Chiang; Kuo-Cheng Lu (EPMA Journal, 2013)
Background Patients on chronic hemodialysis (HD) have impaired cellular and humoral immunity. The percentage of elderly people among the total population in Taiwan is increasing dramatically, and HD is the primary alternative for renal replacement therapy when renal function declines. Activated vitamin D is widely used in HD patients with secondary hyperparathyroidism (SHPT) and is a well-known immunomodulatory agent. Personalized medicine and integrative medical approach has been a trend in current clinical practice. Can we improve their immune function using vitamin D in spite of the mineral aspect? Here, we investigated the relationship between serum 25-hydroxyvitamin D (25(OH)D) level and T cell differentiation in chronic HD patients. Methods Forty patients with chronic HD were enrolled. HD patients with SHPT had been treated with activated vitamin D for 3 months. Peripheral blood mononuclear cells obtained from the patients were cultured and stimulated by mitogens, and T cells were analyzed by flow cytometry. Serum 25(OH)D levels were detected by enzyme-linked immunosorbent assay. Results The incidence of T cell differentiation to the T helper cell (Th)2 subtype was more prevalent in the elderly group than in the controls ( p = 0.001). Th2 differentiation was also correlated with age ( p = 0.004) and serum 25(OH)D levels ( p < 0.05). After treated with activated vitamin D, the level of Th1 cytokines decreased while the Th2 cytokine level increased in the sera ( p < 0.05). The T cell differentiation tended toward the Th2 subtype ( p = 0.027) after treatment of activated vitamin D in SHPT patients. Conclusions These results demonstrated that Th2 differentiation is correlated with age and the serum 25(OH)D level of patients. Treatment with activated vitamin D influenced T cell differentiation and cytokine expression in SHPT patients. Taking vitamin D is the possible prediction and targeted treatment in the immune dysfunction in chronic HD patients.

Development of medium- and low-rise reinforced concrete building fragility curves based on Chi-Chi Earthquake data - Meng-Hsun Hsieh; Bing-Jean Lee; Tsu-Chiang Lei; Jer-Yan Lin (Natural Hazards, 2013)

Emission factor of exhaust gas constituents during the pyrolysis of zinc chloride immersed biosolid - Hung-Lung Chiang; Kuo-Hsiung Lin; Hua-Hsien Chiu (Environmental Science and Pollution Research, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

Cell Hypertrophy and MEK/ERK Phosphorylation are Regulated by Glyceraldehyde-Derived AGEs in Cardiomyocyte H9c2 Cells - Shun-Yao Ko; I-Hsuan Lin; Tzong-Ming Shieh; Hsin-An Ko; Hong-I Chen; Tzong-Cherng Chi; Shu-Shing Chang; Yi-Chiang Hsu (Cell Biochemistry and Biophysics, 2013)

Application of a feature-based approach to debris flow detection by numerical simulation - Chih-Wei Lin; Cheng-Wu Chen; Wen-Ko Hsu; Chia-Yen Chen; Chung-Hung Tsai; Yi-Ping Hung; Wei-Ling Chiang (Natural Hazards, 2013)

Predictors of First-Week Mortality in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shang-Lin Chiang; Heng-Yi Chu; Shin-Tsu Chang; Liang-Cheng Chen (The Cerebellum, 2013)

The construction of a high-resolution visual monitoring for hazard analysis - Chi-Wei Lin; Yi-Ping Hung; Wen-Ko Hsu; Wei-Ling Chiang; Cheng-Wu Chen (Natural Hazards, 2013)

β2-Glycoprotein I inhibits VEGF-induced endothelial cell growth and migration via suppressing phosphorylation of VEGFR2, ERK1/2, and Akt - Wen-Chin Chiu; Jan-Yu Lin; Tzong-Shyuan Lee; Li-Ru You; An-Na Chiang (Molecular and Cellular Biochemistry, 2013)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Development of transgenic watermelon resistant to Cucumber mosaic virus and Watermelon mosaic virus by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Yi-Hua Chiang; Hsiu-Yin Ho; Tsong-Ann Yu; Fuh-Jyh Jan (Transgenic Research, 2012)

Functional redundancy of the two 5-hydroxylases in monolignol biosynthesis of Populus trichocarpa: LC–MS/MS based protein quantification and metabolic flux analysis - Jack P. Wang; Christopher M. Shuford; Quanzi Li; Jina Song; Ying-Chung Lin; Ying-Hsuan Sun; Hsi-Chuan Chen; Cranos M. Williams; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2012)

Impact of MCP-1 and CCR-2 gene polymorphisms on coronary artery disease susceptibility - Hsiu-Ling Lin; Kwo-Chang Ueng; Yih-Shou Hsieh; Whei-Ling Chiang; Shun-Fa Yang; Shu-Chen Chu (Molecular Biology Reports, 2012)

Stream discharge characteristics through urbanization gradient in Danshui River, Taiwan: perspectives from observation and simulation - Jr-Chuan Huang; Chun-Chiang Lin; Shih-Chien Chan; Tsung-Yu Lee; Shih-Chieh Hsu; Cheing-Tung Lee; Jiun-Chuan Lin (Environmental Monitoring and Assessment, 2012)

Niacin improves ischemia-induced neovascularization in diabetic mice by enhancement of endothelial progenitor cell functions independent of changes in plasma lipids - Po-Hsun Huang; Chih-Pei Lin; Chao-Hung Wang; Chia-Hung Chiang; Hsiao-Ya Tsai; Jia-Shiong Chen; Feng-Yen Lin; Hsin-Bang Leu; Tao-Cheng Wu; Jaw-Wen Chen; Shing-Jong Lin (Angiogenesis, 2012)

Synergistic effects of streptolysin S and streptococcal pyrogenic exotoxin B on the mouse model of group A streptococcal infection - Chih-Hsin Hung; Nina Tsao; Yi-Fang Zeng; Shiou-Ling Lu; Chuan Chiang-Ni; Yee-Shin Lin; Jiunn-Jong Wu; Chih-Feng Kuo (Medical Microbiology and Immunology, 2012)

A System Dynamic Model and Sensitivity Analysis for Simulating Domestic Pollution Removal in a Free-Water Surface Constructed Wetland - Yung-Chieh Wang; Yu-Pin Lin; Chun-Wei Huang; Li-Chi Chiang; Hone-Jay Chu; Wen-Sheng Ou (Water, Air, & Soil Pollution, 2012)

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

Assessing Taiwan’s energy security under climate change - Shih-Mo Lin; Jun-Chiang Feng; Fu-Kuang Ko (Natural Hazards, 2012)

The backend design of an environmental monitoring system upon real-time prediction of groundwater level fluctuation under the hillslope - Hsueh-Chun Lin; Yao-Ming Hong; Yao-Chiang Kan (Environmental Monitoring and Assessment, 2012)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

Correlating recurrent radon precursors with local earthquake magnitude and crust strain near the Chihshang fault of eastern Taiwan - T. Kuo; C. Lin; C. Su; C. Liu; C. H. Lin; C. Chang; C. Chiang (Natural Hazards, 2011)

Relationship between temperature change and the requirement for a permanent pacemaker implantation in bradyarrhythmias - I-Fan Liu; Shih-Lin Chang; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Chi-Woon Kong; Tsu-Juey Wu; Chern-En Chiang; Shih-Ann Chen; Yenn-Jiang Lin (International Journal of Biometeorology, 2011)

Mitochondrial proteomics analysis of tumorigenic and metastatic breast cancer markers - Yi-Wen Chen; Hsiu-Chuan Chou; Ping-Chiang Lyu; Hsien-Sheng Yin; Fang-Liang Huang; Wun-Shaing Wayne Chang; Chiao-Yuan Fan; I-Fan Tu; Tzu-Chia Lai; Szu-Ting Lin; Ying-Chieh Lu; Chieh-Lin Wu; et al. (Functional & Integrative Genomics, 2011)

Bacteria associated with an encrusting sponge ( Terpios hoshinota ) and the corals partially covered by the sponge - Sen‐Lin Tang; Mei‐Jhu Hong; Ming‐Hui Liao; Wann‐Neng Jane; Pei‐Wen Chiang; Chung‐Bin Chen; Chaolun A. Chen (Environmental Microbiology, 2011)
Summary Terpios hoshinota , a dark encrusting sponge, is known to be a competitor for space in coral reef environments, and facilitates the death of corals. Although numerous cyanobacteria have been detected in the sponge, little is known of the sponge‐associated bacterial community. This study examined the sponge‐associated bacterial community and the difference between the bacterial communities in the sponge and the coral partially covered by the sponge by analysis of 16S rRNA gene sequences of samples isolated from the sponge covering the corals Favia complanata, Isopora palifera, Millepora sp. , Montipora efflorescens and Porites lutea . The sponge‐associated bacterial community was mainly (61–98%) composed of cyanobacteria, with approximately 15% of these alphaproteobacteria and gammaproteobacteria, although the proportions varied in different sponge samples. The dominant cyanobacteria group was an isolated group closely related to Prochloron sp. The comparison of the bacterial communities isolated from sponge‐free and the sponge‐covered P. lutea showed that covering by the sponge caused changes in the coral‐associated bacterial communities, with the presence of bacteria similar to those detected in black‐band disease, suggesting the sponge might benefit from the presence of bacteria associated with unhealthy coral, particularly in the parts of the coral closest to the margin of the sponge.

Population structure of Nouelia insignis (Asteraceae), an endangered species in southwestern China, based on chloroplast DNA sequences: recent demographic shrinking - Xun Gong; Shan-Shan Luan; Kuo-Hsiang Hung; Chi-Chuan Hwang; Chung-Jean Lin; Yu-Chung Chiang; Tzen-Yuh Chiang (Journal of Plant Research, 2011)

How can electronics industries become green manufacturers in Taiwan and Japan - Shih-Yuan Chiang; Chiu-Chi Wei; Te-Hsuan Chiang; Wei-Lin Chen (Clean Technologies and Environmental Policy, 2011)

Anti-herpes simplex virus effects of berberine from Coptidis rhizoma, a major component of a Chinese herbal medicine, Ching-Wei-San - Lengsu William Chin; Yu-Wen Cheng; Shih-Shen Lin; Ya-Yun Lai; Long-Yau Lin; Ming-Yung Chou; Ming-Chih Chou; Chi-Chiang Yang (Archives of Virology, 2010)

Cost Considerations in Choosing Group Size for Group Testing in the Seed Potato Certification Program - Kuo-Szu Chiang; Sin-Hong Lai; Wen-Chuan Chung; Shang-Hu Lin; Tso-Chi Yang (American Journal of Potato Research, 2010)

Multiple factors have shaped the phylogeography of Chinese spiny loach Cobitis sinensis in Taiwan as inferred from mitochondrial DNA variation - T.‐Y. Chiang; H.‐D. Lin; K.‐T. Shao; K.‐C. Hsu (Journal of Fish Biology, 2010)
Mitochondrial DNA cytochrome b sequences (1140 bp) in 61 specimens of Chinese spiny loach Cobitis sinensis from 12 drainages in Taiwan were identified as two major clades, exhibiting a southern and a northern distribution, north of TzengWen and south of TzengWen (including TzengWen), respectively. The divergence time between these two phylogroups was estimated at 7·34–9·06 million years before present ( b.p. ), but these two phylogroups were formed c. 3·41–4·23 and 2·22–2·75 M b.p. , respectively. Moreover, geological events have been recalculated that Taiwan Island emerged above sea level at an estimate of c . 4–5 M b.p. , and quickly became its present shape at c. 2 M b.p. through mountain building. These results suggest that these two major clades of C. sinensis in Taiwan might originate from two different continental populations, since the island's initial isolation in the Pliocene. Within southern Taiwan, the initial colonization was hypothesized to be in KaoPing River, followed by its northward dispersal. The high divergence between KaoPing and TzengWen was influenced by glaciations and landforms. Within north Taiwan, the colonization was from the Miaoli Plateau through western Taiwan to north‐eastern and northern Taiwan. This dispersal pattern is concordant with the previously proposed hypothesis. Apparently, both geological and phylogeographic evidence suggested that river capture of the upper Takia River by the LanYang River promoted range expansion in freshwater fishes and also indicated that the Central Range within Taiwan did not act as a barrier to the dispersal of C. sinensis .

Monoamine oxidase A gene polymorphisms and enzyme activity associated with risk of gout in Taiwan aborigines - Hung-Pin Tu; Albert Min-Shan Ko; Shu-Jung Wang; Chien-Hung Lee; Rod A. Lea; Shang-Lun Chiang; Hung-Che Chiang; Tsu-Nai Wang; Meng-Chuan Huang; Tsan-Teng Ou; Gau-Tyan Lin; Ying-Chin Ko (Human Genetics, 2010)

Phylogeography of Hemibarbus labeo (Cyprinidae): secondary contact of ancient lineages of mtDNA - Chung‐Jian Lin; Hung‐Du Lin; Jiang‐Ping Wang; Seau‐Chiou Chao; Tzen‐Yuh Chiang (Zoologica Scripta, 2010)
Lin, C.‐J., Lin, H.‐D., Wang, J.‐P., Chao, S.‐C. & Chiang, T.‐Y. (2007). Phylogeography of Hemibarbus labeo (Cyprinidae): secondary contact of ancient lineages of mtDNA. — Zoologica Scripta, 39 , 23–35. Nucleotide sequences of the D‐loop control region of mtDNA were used to assess the genetic structure and phylogeography of Hemibarbus labeo in Mainland China and Taiwan. A hierarchical analysis of molecular variance of populations in 11 major streams from three geographical regions revealed significant structuring among populations and geographical regions. High levels of nucleotide diversity ( π = 1.88%) and haplotype diversity ( h = 96 ± 0.009%) suggest a large effective population size. A maximum likelihood tree based on mtDNA variation identified two ancient mtDNA lineages, which split approximately 3.39 million years ago. Overlapping distribution of the major lineages displayed low correspondence with geographical regions and reflects a scenario of secondary mergence after long isolation. Gene genealogy further revealed a unidirectional migration. Nevertheless, there existed a phylogeographical structure that mostly agreed with a biogeographical hypothesis. That is, within each lineage, a close phylogeny between populations of the River‐Campagna and East‐Pacific regions was supported by the mtDNA gene genealogy, although monophyly of each geographical region was not supported. The degree of genetic differentiation was correlated with geographical distances between populations, displaying a pattern of ‘isolation by distance’. Gene genealogy of mtDNA revealed that Yangtzejiang population may act as a divergence centre of H. labeo . In addition, Taiwan population was colonized via a recent a founder event, likely from population Yangtzejiang River about 131 000 years before present. Low haplotype number and genetic variability also suggested possible bottleneck events in the Rongjiang and Dazhangjiang populations.

Therapeutic potential of olfactory ensheathing cells in neurodegenerative diseases - Shao-Chih Chiu; Huey-Shan Hung; Shinn-Zong Lin; Esheral Chiang; Demeral David Liu (Journal of Molecular Medicine, 2009)

Trophic coupling between Synechococcus and pigmented nanoflagellates in the coastal waters of Taiwan, western subtropical Pacific - Lin Yun-Chi; Tsai An-Yi; Chiang Kuo-Ping (Journal of Oceanography, 2009)

Production of cyclodextrin glucanotransferase from an alkalophilic Bacillus sp. by pH-stat fed-batch fermentation - Chou-Chiang Kuo; Ching-An Lin; Jing-Yi Chen; Ming-Tse Lin; Kow-Jen Duan (Biotechnology Letters, 2009)

Antagonism between abscisic acid and ethylene in Arabidopsis acts in parallel with the reciprocal regulation of their metabolism and signaling pathways - Wan-Hsing Cheng; Ming-Hau Chiang; San-Gwang Hwang; Pei-Chi Lin (Plant Molecular Biology, 2009)

Isolation and characterization of 15 microsatellite loci from Caridina gracilipes (Atyidae, Decapoda) - Chiao-Chuan Han; Cheng-Sheng Chang; Tzen-Yuh Chiang; Ping-Han Chung; Hung-Du Lin (Conservation Genetics, 2009)

An ANN–RTS smoother scheme for accurate INS/GPS integrated attitude determination - Kai-Wei Chiang; Yung-Cheng Lin; Yun-Wen Huang; Hsiu-Wen Chang (GPS Solutions, 2009)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

Isolation and characterization of polymorphic microsatellite loci in Candidia barbata (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Yu-Min Ju; Lee-Shing Fang; Chung-Jian Lin (Conservation Genetics, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Isolation and characterization of microsatellite loci in the commercially important mudshrimp Austinogebia edulis (Upogebiidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Hung-Du Lin; Tin-Yam Chan; Cheng-Yu Hung; Feng-Jiau Lin (Conservation Genetics, 2008)

Synergic Co-activation in Forearm Pronation - Shyang Chang; Ming-Chun Hsyu; Hsiu-Yao Cheng; Sheng-Hwu Hsieh; Chen-Chiang Lin (Annals of Biomedical Engineering, 2008)

Isolation and characterization of microsatellite loci in the endangered freshwater fish Varicorhinus alticorpus (Cyprinidae) - Tzen-Yuh Chiang; Teh-Wang Lee; Feng-Jiau Lin; Kuo-Hua Huang; Hung-Du Lin (Conservation Genetics, 2008)

Isolation and characterization of 11 polymorphic microsatellite loci from Fatsia polycarpa (Araliaceae), an element of evergreen forests in Taiwan - Chi-Chun Huang; Kuo-Hsiang Hung; Tsai-Wen Hsu; Kuo-Hsiung Wang; Chi-Yung Lin; Tzen-Yuh Chiang (Conservation Genetics, 2008)

Isolation and characterization of microsatellite loci in the endangered freshwater fish Pararasbora moltrechti (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Hung-Du Lin; Teh-Wang Lee; Fang-Jiao Lin; Chung-Jian Lin; Tzen-Yuh Chiang (Conservation Genetics, 2008)

Population structure and phylogeography of Aphyocypris kikuchii (Oshima) based on mitochondrial DNA variation - H.‐D. Lin; K.‐C. Hsu; K.‐T. Shao; Y.‐C. Chang; J.‐P. Wang; C.‐J. Lin; T.‐Y. Chiang (Journal of Fish Biology, 2008)
Aphyocypris kikuchii is a cyprinid species endemic to northern and eastern Taiwan and is the only primary freshwater fish native east of the Coastal Mountain Range. In total, 92 individuals of A. kikuchii from seven populations in three regions of the island were surveyed for mitochondrial DNA (mtDNA) variation. High haplotype diversity ( h = 0·989) and low nucleotide diversity ( π = 0·009) of mtDNA were detected. Negative values of Tajima’s D and unimodal mismatch distributions probably reflect a history of recent demographic expansions from small populations. Three major haplotype clusters displayed geographically non‐overlapping distributions, indicating a long‐term isolation between regions. Hierarchical analysis of molecular variance showed significant genetic structuring among populations ( Φ ST = 0·66). Significant haplotype heterogeneity was also detected among populations within regions ( Φ SC = 0·41, P Φ CT = 0·43, P c. 0·11–0·39 million years ago. Haplotypes of cluster B nested as interior nodes in the haplotype network, indicating that migrations from Shueilian (SL) populations to the northern region (cluster A) and to the eastern region (cluster C) may have occurred independently. Lineages A and B + C should be managed as two distinct evolutionarily significant units, while the northern, SL and southern groups should be managed as separate management units.

Elucidation of susceptible factors to endoplasmic reticulum stress-mediated anticancer activity in human hepatocellular carcinoma - Po-Cheng Chiang; Jui-Ling Hsu; Ting-Chun Yeh; Shiow-Lin Pan; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Activation of p53 by Dishevelled independent of Wnt or planar polarity pathways - Vivianne W. Ding; Li-Ping Lin; Andrew L. Chiang; Frank McCormick (Journal of Molecular Medicine, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genetic analysis of an attenuated Papaya ringspot virus strain applied for cross-protection - Chu-Hui Chiang; Chun-Yee Lee; Ching-Hsien Wang; Fuh-Jyh Jan; Shih-Shun Lin; Tsung-Chi Chen; Joseph A. J. Raja; Shyi-Dong Yeh (European Journal of Plant Pathology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

Assessing Impacts of Typhoons and the Chi-Chi Earthquake on Chenyulan Watershed Landscape Pattern in Central Taiwan Using Landscape Metrics - Yu-pin Lin; Tsun-kuo Chang; Chen-fa Wu; Te-chih Chiang; Shin-hwei Lin (Environmental Management, 2006)

Streptococcal pyrogenic exotoxin B causes mitochondria damage to polymorphonuclear cells preventing phagocytosis of Group A streptococcus - Chuan Chiang-Ni; Chih-Hung Wang; Pei-Jane Tsai; Woei-Jer Chuang; Yee-Shin Lin; Ming-T. Lin; Ching-Chuan Liu; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2006)

Investigation of Mtbe and Aromatic Compound Concentrations at a Gas Service Station - Chi-Wen Lin; Song-Bor Chiang; San-Ju Lu (Environmental Monitoring and Assessment, 2005)

Anti-hepatitis B surface antigen IgG1 subclass is predominant in individuals who have recovered from hepatitis B virus infection, chronic carriers and vaccinees - Lina Wang; Shyh-Jye Lin; Ju-Hsin Tsai; Chung-Hung Tsai; Chung-Chuan Tsai; Chi-Chiang Yang (Medical Microbiology and Immunology, 2005)

Fine-tuning risperidone dosage for acutely exacerbated schizophrenia: clinical determinants - Hsien-Yuan Lane; Yue-Cune Chang; Chih-Chiang Chiu; Sue-Hong Lee; Cher-Yeang Lin; Wen-Ho Chang (Psychopharmacology, 2004)

Site-Directed Mutagenesis of the Conserved Threonine, Tryptophan, and Lysine Residues in the Starch-Binding Domain of Bacillus sp. Strain TS-23 a-Amylase - Huei-Fen Lo; Wen-Ying Chiang; Meng-Chun Chi; Hui-Yu Hu; Long-Liu Lin (Current Microbiology, 2004)

Isolation and characterization of microsatellite loci in Acrossocheilus paradoxus (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Kui-Ching Hsu; Jiang-Ping Wang; Xiang-Lin Chen; Tzen-Yuh Chiang (Conservation Genetics, 2004)

Inhibition of return in children with attention deficit hyperactivity disorder - Chiang-Shan Ray Li; Hsueh-Ling Chang; Shih-Chieh Lin (Experimental Brain Research, 2003)

Replacement of Methionine 208 in a Truncated Bacillus sp. TS-23 α-Amylase with Oxidation-Resistant Leucine Enhances Its Resistance to Hydrogen Peroxide - Long-Liu Lin; Huei-Fen Lo; Wen-Ying Chiang; Hui-Yu Hu; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2003)

Deletion analysis of the C-terminal region of the α-amylase of Bacillus sp. strain TS-23 - Huei-Fen Lo; Long-Liu Lin; Wen-Ying Chiang; Meng-Chun Chie; Wen-Hwei Hsu; Chen-Tien Chang (Archives of Microbiology, 2002)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

The spectrum of microsatellite loci on chromosomes 7 and 8 in Taiwan aboriginal populations: a comparative population genetic study - Chi-Chen Wei; Fu-Tien Chiang; Kuo-Sin Lin; L.-I. Lin (Human Genetics, 1999)

Longitudinal changes in Ca, Mg, Fe, Cu, and Zn in breast milk of women in Taiwan over a lactation period of one year - Te-Hsien Lin; Yuh-Jyh Jong; Chi-Hsiun chiang; Mo-Hsiung Yang (Biological Trace Element Research, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Human T-lymphotropic Virus Type II Infection inVietnamese Thalassemic Patients - M. T. Lin; B. T. Nguyen; T. V. Binh; T. V. Be; T. Y. Chiang; L. H. Tseng; Y. C. Yang; K. H. Lin; Y. -C. Chen (Archives of Virology, 1997)

A long lytic cycle in filamentous phage Cf1tv infectingXanthomonas campestris pv.citri - T. -T. Kuo; C. -C. Chiang; S. -Y. Chen; J. -H. Lin; J. -L. Kuo (Archives of Virology, 1994)